SEDIMENT DEPOSITION PROPAGATION AND QUALITY DISTRIBUTION ANALYSIS OF SANDSTONE RESERVOIR AT COMPARTMENTALIZED âHNâ FIELD IN JAMBI SUB-BASIN USING SEISMIC ATTRIBUTES METHOD - Nur Syarifah, Raihanah
“HN” Field in Jambi Sub-Basin has a target reservoir of sandstone in the Lower Talang Akar formation which is compartmentalized due to the fault into three main parts. The existence of fault influenced the depositional propagation of the sediments that filled the basin at that time. As a result, each compartment will have different depositional propagation which makes the distribution of reservoir quality will also different. This study aims to identify sediment deposition propagation and distribution of sandstone reservoir quality as a result of compartmentalization that occurred in the field. The research was conducted using 3D PSTM seismic data with 64 wells divided into three main compartments. Based on the tuning thickness analysis, the individual thickness of sandstone in the formation is tend to be thin and under the vertical seismic resolution. As an alternative, the study then used an approach to identify the sandstone in a “package” consist in Lower Talang Akar Formation (LTAF) namely upper LTAF, middle LTAF, and lower LTAF. Each of those identified sandstone reservoir dominantly falls on a negative reflector so that the Sum of Negative Amplitude attribute is chosen to map the quality of the sandstone reservoir itself. Based on the analysis of the log data, the depositional environment in the LTAF is braided river at Simpang, meandering river at Lower LTAF , and anastomosing rivers (coastal plain) at Upper and Middle LTAF. The direction of sediment depositional propagation is NE-SW and N-S, which determined based on the delineation relative to the sand thickness map in the area considered as the channel fill deposits. As for mapping the quality of the sandstone reservoir, it was found that there is an indirect relationship between depth, sandstone thickness, sand/shale ratio, and CO2 content, where in deeper areas, the sandstone tends to be thick, the sand/shale ratio is large, and the CO2 content is high.